Isolasi, Uji Fitokimia Dan Aktivitas Antibakteri Jamur Endofit Bunga Sambiloto (Andrographis Paniculata) - Rani Aulia Suhanah; Suryelita Thaher; Melindra Mulia (Jurnal Periodic Jurusan Kimia UNP, 2022)
Endophytic fungi are microorganisms that live in plant tissues without harming the host plant. One of the plants that have potential as a host for endophytic fungi is the flower of the bitter plant (Andrographis paniculata) which contains secondary metabolites and has biological activity. The purpose of this study was to obtain fungal isolates and identify the content of secondary metabolites and antibacterial activity. The results of the isolation of endophytic fungi produced isolates of endophytic fungi with isolate code BS. Microscopic observation of BS isolates belonging to Chrysosporium spp. The results of the phytochemical test of the ethyl acetate extract were positive for terpenoid compounds marked with a pink color and the FTIR spectrum containing a dimethyl gem group. BS extract also could inhibit the growth of all test bacteria, namely E. coli and S. aureus at concentrations of 1%, 3%, and 5%.